Subjective Games and Equilibria: I+ - Ehud Kalai; Ehud Lehrer (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
Applying the concepts of Nash, Bayesian or correlated equilibrium to analysis of strategic interaction, requires that players possess objective knowledge of the game and opponents' strategies. Such knowledge is often not available. The proposed notions of subjective games, and subjective Nash and correlated equilibria, replace unavailable objective knowledge by subjective assessments. When playing such a game repeatedly, subjective optimizers will converge to a subjective equilibrium. We apply this approach to some well known examples including a single multi-arm bandit player, multi-person mulit-arm bandit games, and repeated Cournot oligopoly games.
Keywords: 330